Qualitative Profiling and Quantification of Neonicotinoid Metabolites in Human Urine by Liquid Chromatography Coupled with Mass Spectrometry - Taira, Kumiko; Fujioka, Kazutoshi; Aoyama, Yoshiko (PLOS ONE, 2013)
Neonicotinoid pesticides have been widely applied for the production of fruits and vegetables, and occasionally detected in conventionally grown produce. Thus oral exposure to neonicotinoid pesticides may exist in the general population; however, neonicotinoid metabolites in human body fluids have not been investigated comprehensively. The purpose of this study is the qualitative profiling and quantitative analysis of neonicotinoid metabolites in the human spot urine by liquid chromatography coupled with mass spectrometry (LC/MS). Human urine samples were collected from three patients suspected of subacute exposure to neonicotinoid pesticides. A qualitative profiling of urinary metabolites was performed using liquid chromatography/time-of-flight mass spectrometry (LC/TOFMS) with a database of nominal molecular weights of 57 known metabolites of three neonicotinoid pesticides (acetamiprid, Imidacloprid, and clothianidin), as well as the parent compounds. Then a quantitative analysis of selected urinary metabolites was performed using liquid chromatography/tandem mass spectrometry (LC/MS/MS) with a standard pesticide and metabolite, which were detected by the qualitative profiling. The result of qualitative profiling showed that seven metabolites, i.e. an acetamiprid metabolite, N-desmethyl-acetamiprid; three Imidacloprid metabolites, 5-hydroxy-Imidacloprid, 4,5-dihydroxy-imidacloprid, 4,5-dehydro-Imidacloprid; a common metabolite of acetamiprid and Imidacloprid, N-(6-chloronicotinoyl)-glycine; and two clothianidin metabolites, N-desmethyl-clothianidin, N-(2-(methylsulfanyl)thiazole-5-carboxyl)-glycine, as well as acetamiprid, were detected in the urine of three cases. The result of the quantitative analysis showed N-desmethyl-acetamiprid was determined in the urine of one case, which had been collected on the first visit, at a concentration of 3.2 ng/mL. This is the first report on the qualitative and quantitative detection of N-desmethyl-acetamiprid in the human urine. The results suggest that the one case with detection of N-desmethyl-acetamiprid was exposed to acetamiprid through the consumption of contaminated foods. Urinary N-desmethyl-acetamiprid, as well as 5-hydroxy-Imidacloprid and N-desmethyl-clothianidin, may be a good biomarker for neonicotinoid exposure in humans and warrants further investigation.